Hubungan Perilaku Keluarga Dengan Pencegahan Kejadian Demam Berdarah Dengue (DBD) Di Kelurahan Jambangan Kota Surabaya - Andi Jayawardhana; Roby Aji Permana; Yus Kogoya (2019)
Dengue Hemorrhagic Fever (DHF) still occurs in Indonesia. This disease can affect everyone, especially in children. To prevent dengue disease most important is to control the aedes aegypti mosquito as the main vector. Prevention is the program of Eradication Mosquito Nest (PSN) by physical and chemical. Eradication and prevention of disease is needed a good behavior on the community, so that disease prevention efforts can run well. The purpose of this research is to know